Profiling of human acquired immunity against the salivary proteins of Phlebotomus papatasi reveals clusters of differential immunoreactivity - Geraci, Nicholas S.; Mukbel, Rami M.; Kemp, Michael T.; Wadsworth, Mariha N.; Lesho, Emil; Stayback, Gwen M.; Champion, Matthew M.; Bernard, Megan A.; Abo-Shehada, Mahmoud; Coutinho-Abreu, Iliano V.; Ramalho-Ortigão, Marcelo; Hanafi, Hanafi A.; et al. (My University, 2014)
Phlebotomus papatasi sand flies are among the primary vectors of Leishmania major parasites from Morocco to the Indian subcontinent and from southern Europe to central and eastern Africa. Antibody-based immunity to sand fly salivary gland proteins in human populations remains a complex contextual problem that is not yet fully understood. We profiled the immunoreactivities of plasma antibodies to sand fly salivary gland sonicates (SGSs) from 229 human blood donors residing in different regions of sand fly endemicity throughout Jordan and Egypt as well as 69 US military personnel, who were differentially exposed to P. papatasi bites and L. major infections in Iraq. Compared with plasma from control region donors, antibodies were significantly immunoreactive to five salivary proteins (12, 26, 30, 38, and 44 kDa) among Jordanian and Egyptian donors, with immunoglobulin G4 being the dominant anti-SGS isotype. US personnel were significantly immunoreactive to only two salivary proteins (38 and 14 kDa). Using k-means clustering, donors were segregated into four clusters distinguished by unique immunoreactivity profiles to varying combinations of the significantly immunogenic salivary proteins. SGS-induced cellular proliferation was diminished among donors residing in sand fly-endemic regions. These data provide a clearer picture of human immune responses to sand fly vector salivary constituents.
Citation: Geraci, Nicholas S., Rami M. Mukbel, Michael T. Kemp, Mariha N. Wadsworth, Emil Lesho, Gwen M. Stayback, Matthew M. Champion, et al. 2014. “Profiling of Human Acquired Immunity Against the Salivary Proteins of Phlebotomus Papatasi Reveals Clusters of Differential Immunoreactivity.” The American Journal of Tropical Medicine and Hygiene 90 (5): 923–38. https://doi.org/10.4269/ajtmh.13-0130.
Keywords: Phlebotomus papatasi; Sand flies; Leishmania major; Sand fly salivary gland proteins; Antibody-based immunity; Human immune responses